(untitled) (Research, Society and Development, 2020)
This article aims to evaluate the hygienic and sanitary quality of 60 samples of vegetables (Lactuca sativa and Nasturtium officinale) of conventional and hydroponic cultivation commercialized in São Luís (MA) and to evaluate the efficiency of conventional sanitizers. Microbiological analyses were performed based on the methodology described in the Compendium of Methods for the Microbiological Examination of Foods - APHA. Of the 60 samples analyzed, 95.00% (n=57) were in disagreement with the current legislation for coliforms at 45°C, and the presence of Escherichia coli was identified in both vegetables. All sanitizers presented inhibitory potential. Therefore, the satisfactory results obtained in this study ensure the use of sanitizers, emphasizing their viable cost, efficient and fast application.